Understanding the Response to High-Stakes Incentives in Primary Education - Maximilian Bach; Mira Fischer (Institute of Labor Economics (IZA), 2020)
This paper studies responses to high-stakes incentives arising from early ability tracking. We use three complementary research designs exploiting differences in school track admission rules at the end of primary school in Germany's early ability tracking system. Our results show that the need to perform well to qualify for a better track raises students' math, reading, listening, and orthography skills in grade 4, the final grade before students are sorted into tracks. Evidence from self-reported behavior suggests that these effects are driven by greater study effort but not parental responses. However, we also observe that stronger incentives decrease student well-being and intrinsic motivation to study.
Keywords: I20; I28; I29; 330; student effort; tracking; incentives